Sindhenan in Karawitan Arts - Karoso, Subianto (Proceeding Series of International Conference on Arts and Humanities, 2021)
Sindhenan is a part of Karawitan arts which improves the sense of aesthetic in the music art. Sindhenan is a vocal practice following the rhythm of gamelan music with distinctive voicing techniques based on Javanese aesthetic concept. These vocal techniques include the technique of luk, wiled, gregel, angkatan, seleh, and breathing technique. The concept of a quality sindhenan is known as nggendingi meaning which includes mungguh, ngledheki, lelewa, pas, ngenongi, nggandhul, selingan, and andhegan. The vocals are performed by the singers (pesindhen) through a long training that repeatedly adjusts to the sound of the gamelan tuning. Also, some singers or pesindhen sometimes make interesting movements and attitudes while singing. Generally, singers as ensemble and accompaniment of pakeliran style prioritize their voice colour, voicing technique, and vocabulary mastery of the song sentences. Singers are required to always be in prime condition as well as spectacular in their appearance because they are the audience attention. The main function of sindhenan is to enrich the aesthetic value in the performance. A good singer (pesindhen) is required to have wide communication skills and great vocal skills for singing songs (tembang). The presence of a singer is one of determining factors for a success show. The singer is able to bring up a good show through her quality and professionalism such as character, charisma, charm, and a considerable virtuosity in a performance. Empirical reality shows that the presence of singers tends to be the centre of public attention in almost every performance either as karawitan shows or as puppet shows (wayang). The singers who have a good vocal will support the performance of a mastermind (dalang).